ADULTERY IN THE PERSPECTIVE OF ISLAMIC RELIGIOUS LAW AND POSITIVE LAW IN THE INDONESIAN COMMUNITY - Khaerunisa, Farah Edhar (Hunafa: Jurnal Studia Islamika, 2021)
This study aims to examine and find out about the arrangements for adultery in Islamic law and criminal law in Indonesia and to find out the zina sanctions that exist in Islamic religious law and criminal law. The type of data used in this study is secondary data consisting of the Criminal Code, Al-quran, as well as other sources in the form of books and other materials such as journals related to the issues discussed in this. This data collection uses literature study techniques. Data analysis using analysis techniques between content theory. Based on the research that has been done, it can be found that the regulation of adultery in criminal law is contained in Article 284 which states that adultery is a sexual relationship between two perpetrators who are married or one of them is bound by a marriage. In Islamic law, it provides regulations regarding adultery, that every husband and wife relationship outside of a legal marriage we can call adultery, and distinguishes the perpetrator of adultery here into two, namely Ghairu Muhshan: the perpetrator who is not bound by marriage and secondly, Muhsan is the perpetrator who bound by marriage. In this criminal law, it provides sanctions for criminal acts of adultery in the form of a prison sentence of 9 months which must fulfill several existing requirements. Islamic law provides sanctions for criminal acts of adultery in the form of punishments such as 100 lashes and exile for one year for the perpetrator of Ghairu Muhsan, 100 lashes and stoning to death for the perpetrator of Muhsan.